African American Womanhood: A Study of Women’s Life Writings (1861-1910s) - Élise Vallier (Transatlantica)
This article shows the diversity of African American women’s life experiences through the study of the life narratives of seven women who belonged to different social milieus, had distinct regional identities and dissimilar occupations. Drawing on their correspondence, diaries, and autobiographies, this article explores these women’s economic circumstances, their views on men, marriage, their roles as women, wives, and mothers, and the condition of being a woman of color between 1861 and the late 1910s—a period of dramatic change in the history of the United States, particularly regarding the question of women’s rights. Covering the Civil War, Reconstruction, the Progressive Era, and up to the beginning of World War I, this work examines the way these women expressed their self-identities.